Eight Village Councils Endorse a Resolution on Community Bylaws - Gizaw, Desta; Swai, Elirehema (International Crops Research Institute for the Semi-Arid Tropics, 2025)
ResComm has been effectively promoting community-based agroecological practices in eight villages in the Kongwa area since 2021. Later, the program was extended to three communities in the Mpwapwa region. Agroecological practices like Fanya Juu (FJ) and Fanya Chini (FC) contour terraces, Post Emergence Tied Ridges (PETR), Chololo pits, intercropping, and improved sorghum and pigeon pea varieties practiced at the farm and landscape scale have gained traction and support from local communities and district authorities in the second phase of ResComm. Agroecological approaches have been adopted by approximately 8,600 farmers.